An Architecture Proposal for Nested Software Product Lines in the Domain of Mobile and Context-Aware Applications - Marinho, Fabiana G.; Costa, Aline L.; Lima, Francisco F. P.; B. Neto, Joao B.; F. Filho, Joao B. B.; Rocha, Lincoln; Dantas, Valeria L. L.; Andrade, Rossana M. C.; Teixeira, Eldanae; Werner, Claudia (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2010)
The domain of mobile and context-aware applications involves challenging requirements, such as mobility and adaptation, which makes the application development complex for this area. Considering this scenario, we used a nested software product line (SPL) that aims to facilitate the construction of such software by domain decomposition in two levels of analysis. The first concerns the characteristics of a generic SPL for the mobile and context-aware domain. The second is the requirement analysis of a business domain together with characteristics of the generic level. The goal of this paper is to propose a nested SPL.